Illegitimate tasks: A systematic literature review and agenda for future research. - Ding, Haien; Kuvaas, Bård (Work & Stress)
Although expecting to undertake core tasks affirming their professional identity, employees often have to deal with tasks they perceive as unnecessary or unreasonable. The concept of illegitimate tasks captures this phenomenon and has attracted growing attention since its first appearance. Illegitimate tasks have been found to explain unique variance in well-being and strain. Given a burgeoning body of literature, a systematic narrative review of illegitimate tasks is warranted. This review summarises research regarding illegitimate tasks' antecedents (leadership, workplace characteristics, individual characteristics, and job characteristics) and outcomes (emotions, work attitudes and cognition, work behaviour, health and well-being, and interpersonal relationships). In addition, we review work done to date regarding the moderators and mediators of these relationships. Finally, we offer future directions for research.